The judge's discretion to compensate for an arbitrary divorce (Analytical Comparative Study) - Lateef, Najah Naif; Al- Zibare, Nashwan Khalid Salih (Journal of Economic, Administrative and Legal Sciences, 2022)
Divorce is the right of the husband, and is nullified by his unilateral will, and no one can prevent it in its infliction. However, it is a protection for the wife from the abuse and injustice of the husband. Compensation is established for her when his arbitrariness is proven in the divorce. The judge enjoys wide discretionary power in estimating compensation. This study aims to shed light on the most important issue which the judge has discretionary power, such us the issue of compensation for arbitrary divorce and the related provisions contained in the Iraqi Personal Status law No (188) and its amend application in the Kurdistan Region- Iraq. It is worth noting, the Iraqi and Kurdish legislators restricted the judge’s authority in order to assess the wife’s compensation for arbitrary divorce with three conditions: The first is that it must be proven that the husband was abusive in inflicting the divorce. The second is that this abuse causes damages to the wife and her submitting a request for compensation, and submitting a claim for compensation. We have followed the comparative law approach that contained in the two mentioned laws, in addition to following the analytical method for analyzing and commenting about legal texts, with referring to the judicial decisions.The study reached a number of conclusions and recommendations, including:1- Arbitrary divorce is a divorce that the husband contradicts the purpose of the legislator in personal status law, and the husband does this divorce without reason, and the wife’s consent and her request or her misbehave.2- It is possible to rely on the theory of abuse in the use of the right that contained in the Iraqi Civil law as a legal basis for the husband’s obligation to pay the compensation to his wife in the event of his abuse of divorce. According to one of the criteria of the mentioned theory, that the person uses his right that aims only to harm the others, the husband is reluctant to divorce his wife as long as he signs it without reason and intends to harm her; that means he deviates from the purpose for which it was initiated and causes him harm to others, he is obliged to pay compensation. This is because the Iraqi and Kurdish legislators have indicated that the wife is awarded compensation whenever the court finds that she has been harmed due to the husband’s arbitrariness in inflicting divorce.3- We suggest to the Iraqi legislator to amend the text of third Paragraph of Article (39) of the Personal Status Law, and determining the maximum period of wife’s alimony and making it three years instead of two years, in order to protect the rights of the wife,We suggest to the Kurdistan legislator to amend the second Paragraph of Article (17) of the Amending law of the application of Iraqi Personal Status Law No (188) of 1959 in the Kurdistan Region – Iraq, and determining the same period instead of determining the immediate period, by leaving this issue according to the discretionary power of the judge, in order to estimate the compensation according to each case separately.To read the text in the two laws as follows: (If the husband divorced his wife and the court finds that the husband was abusive in her divorce and the wife suffered harm as a result of that; the court, based on the wife’s request, shall award compensation commensurate with his financial condition and degree of arbitrariness, estimated in total, provided that it does not exceed her maintenance for a period of three years in addition to her other fixed rights).
Keywords: arbitrary divorce; the discretion of the judge; estimation of compensation; proof of damage